EFFICIENT MARKET HYPOTHESIS, ABNORMAL RETURN AND ELECTION PERIODS - Altin, Hakan (European Scientific Journal, ESJ, 2015)
According to the efficient market hypothesis, it is impossible for the investors to achieve abnormally high returns. Because the price of an asset includes all available information which may affect the price of the product. Although until 1970’s the efficient market hypothesis were deemed valid, it has been insufficient to explain specific price anomalies experienced within the recent years. One of these particular anomalies is experienced during the election periods. Within the scope of this study, two conclusions were achieved. The first one is that a price anomaly is experienced during the election period and the informed investors are aware of that. Secondly, it goes without saying that it is not possible to explain the financial market volatilities solely by employing the efficient market hypothesis.